2014
DOI: 10.1039/c4ra09639h
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of hairpins and bulged secondary structures of nucleic acids by single incorporation of α,β-D-CNA featuring a gauche(+) alpha torsional angle

Abstract: A constrained dinucleotide unit featuring a gauche(+) alpha torsional angle configuration was used to stabilize DNA hairpin or bulged structures. Large five nucleotides having looped hairpin structures can be stabilized up to +5 degrees C. Depending on the nature of the closing base pair, the increased hairpin stability can be reached through loop moiety preorganization or stem rearrangement induced on the first two base pairs. With an alpha gauche(+) constraint either within or opposite to the bulge, the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In that context, unlike its behaviour into T4-hairpin, the (SC5', SP) -C2NA modification was not well tolerated and did not behave as its -CNA analogue that improved, in the same conditions, the bulge thermal stabilities. 13 In the other bulge construction, where the (SC5', SP) -C2NA faced the growing loop (Table 6), it appeared that this modification conferred to the structures roughly the same thermal stability around 40 ±2°C regardless to the loop size. While for the one to three nucleotides loop the gauche(+) constraint was unfavourable or neutral (…”
Section: Odnmentioning
confidence: 95%
See 3 more Smart Citations
“…In that context, unlike its behaviour into T4-hairpin, the (SC5', SP) -C2NA modification was not well tolerated and did not behave as its -CNA analogue that improved, in the same conditions, the bulge thermal stabilities. 13 In the other bulge construction, where the (SC5', SP) -C2NA faced the growing loop (Table 6), it appeared that this modification conferred to the structures roughly the same thermal stability around 40 ±2°C regardless to the loop size. While for the one to three nucleotides loop the gauche(+) constraint was unfavourable or neutral (…”
Section: Odnmentioning
confidence: 95%
“…These differences could induce a dramatic change of conformational behaviour. Therefore, the analysis of the conformation of this new family of constrained nucleotides was carried out using 1 H, 13 C, 31 P and 2D NMR techniques, in order to determine the sugar puckering preference of each deoxyribose and the geometry of the oxaza-phosphorinane ring.…”
Section: Nmr Structural Study Of C2namentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that restricting the rotational freedom of the sugar phosphate backbone by means of dioxaphosphorinane rings can favour not only the stabilization of the duplex, but also the preorganization of loops and bulges when those structural elements feature unusual torsion angle value sets. This can result in the stabilization of secondary structures (Figure ) …”
Section: Introductionmentioning
confidence: 99%